Mechanisms of Traumatic Brain Injury - Bauer, Derek; Tung, Monica L.; Tsao, Jack W. (Seminars in Neurology, 2015)
The authors describe the mechanisms of traumatic brain injury (TBI), examining in depth the characteristics of closed head, penetrating, and blast-related TBI. Events on a structural as well as cellular level are reviewed. Blast-related brain injury, in particular, affects military service members preferentially, but is also relevant in cases of industrial accidents as well as terrorist events.
Keywords: traumatic brain injury; closed head injury; penetrating traumatic brain injury; blast traumatic brain injury